Pengaruh Model Pembelajaran Probing Prompting Secara Daring Terhadap Hasil Belajar Bahasa Arab Siswa Kelas VIII SMP Qur’an Darul Fattah - Tsurayya Kamilah; M. Wisnu Khumaidi; Rima Ajeng Rahmawati (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2022)
The background of this research is learning Arabic for class VIII students of SMP Qur'an Darul Fattah in the matter of fi'liyah numbers. the majority of students experience a decrease in learning Arabic, among the causes are students who are getting bored with learning boldly, lack of student reciprocity in the learning process so that learning takes place passively. For this reason, researchers chose research using the Probing Prompting learning model. The purpose of this study was to find out and describe whether there was any influence of the probing prompting learning model boldly on the Arabic language learning outcomes of class VIII students of SMP Qur'an Darul Fattah. The sample for this study was VIIIA class of 26 students as the control class and VIIIB of 26 students as the experimental class. In the experimental class the researcher applied the probing prompting learning model five times and in the control class used the lecture method five times. At the fifth meeting students were given questions in the form of multiple choice tests both in the control class and in the experimental class. Data were analyzed using inferential statistical analysis (t-test independent sample t-test). After being analyzed, the results obtained are tcount = 0.357 with a significance level of 0.772 which is smaller than the ttable value = 2.009 for a significance level of 0.05, it means that H0 is accepted and H1 is rejected. Based on these results it can be interpreted that there is no significant influence between learning using the probing prompting learning model boldly on students' Arabic learning outcomes compared to learning using the lecture method.